2013
DOI: 10.3390/ijms14035633
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Profiling Reveals Functional Importance of Sirt2 in Endothelial Cells under Oxidative Stress

Abstract: The NAD+-dependent deacetylases Sirt1 and Sirt2 mediate cellular stress responses and are highly expressed in vascular endothelial cells. In contrast to the well-documented protective actions of Sirt1, the role of endothelial Sirt2 remains unknown. Using cDNA microarray and PCR validation, we examined global gene expression changes in response to Sirt2 knock down in primary human umbilical vein endothelial cells under oxidative stress. We found that Sirt2 knock down changed expression of 340 genes, which are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 40 publications
(53 reference statements)
3
16
0
Order By: Relevance
“…SIRT2 deacetylates receptor-interacting protein (RIP)-1, facilitating cellular necrosis 55 . Consistent with this, in culture, pharmocological inhibition of SIRT2 prevents endothelial cells from H 2 O 2 -induced cell death 56 , suggesting that SIRT2 aggravates cardiovascular diseases. Although SIRT2 was reported to increase longevity in mice 57 , further study is required to determine roles of SIRT2 in vascular aging.…”
Section: Roles Of Sirt Proteins In Vascular Agingsupporting
confidence: 72%
“…SIRT2 deacetylates receptor-interacting protein (RIP)-1, facilitating cellular necrosis 55 . Consistent with this, in culture, pharmocological inhibition of SIRT2 prevents endothelial cells from H 2 O 2 -induced cell death 56 , suggesting that SIRT2 aggravates cardiovascular diseases. Although SIRT2 was reported to increase longevity in mice 57 , further study is required to determine roles of SIRT2 in vascular aging.…”
Section: Roles Of Sirt Proteins In Vascular Agingsupporting
confidence: 72%
“…We also show an up‐regulation of HSP27 and P‐HSP27. Wild‐type HSP27 lowers the levels of ROS by raising intracellular glutathione (36), whereas P‐HSP27 prevents apoptosis interfering with the caspase cascade (33). In addition, HSP27 maintains the stability of actin fibers (37), a function that might be relevant under gravitational unloading to preserve the remaining components of the cytoskeleton.…”
Section: Resultsmentioning
confidence: 99%
“…Cardus et al showed that SIRT6 depletion by RNA interference in HUVECs and aortic endothelial cells reduced cell proliferation, increased the fraction of senescence‐associated β‐galactosidase‐positive cells, and diminished the ability of the cells to form tubule networks on Matrigel. Finally, Liu et al found that the pharmacologic inhibition of SIRT2 attenuates oxidant‐induced cell toxicity in endothelial cells. Collectively, these data emphasize the important protective role of sirtuins, especially SIRT1, in endothelial cells; preliminary data are emerging about a functionally important role of other sirtuins in endothelial protection.…”
Section: Aging In the Vascular Systemmentioning
confidence: 99%